Empowering society and culinary MSMEs for sustainable development goals initiatives in West Java - Nadia Amanah; Boni Sena; Bobie Suhendra; Ardiansyah Yatim; Sheikh Ahmad Zaki (Journal of Sustainable Tourism and Entrepreneurship, 2024)
Purpose: This study aimed to explore the impact of empowering society and culinary MSMEs on Sustainable Development Goals (SDGs) in West Java, focusing on Sindangmukti Village, Karawang Regency. While prior research has often used a top-down approach, neglecting direct societal impact, this study takes a bottom-up perspective, aligning with implicit SDG principles observed in community services. Research Methodology:  The study employed online questionnaires with 505 households in West Java to evaluate water consumption, waste generation, and energy usage patterns. Specific investigations in Sindangmukti Village have measured community service effectiveness regarding SDGs. Results: The study found that Only 19.1% of the participants set AC temperatures within the recommended ranges. Additionally, initiatives to promote a sustainable city strategy and establish energy-efficient culinary MSMEs in Sindangmukti Village resulted in a 29% increase in knowledge among 70 participants and generated $36.71 income from bitter melon chip production within two months. Limitations: However, the study focused solely on Sindangmukti Village, neglecting the diverse cultural and problem landscapes of other villages in the Karawang Regency. Contributions: The findings of this study can inform future efforts to enhance energy, water, and waste efficiency in residential buildings in West Java, thereby fostering awareness of energy conservation, environmental sustainability, and economic resilience.